“Focus Group Discussion” dalam Paradigma Pembangunan Partisipatif - Dedeh Fardiah (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2005)
Some recent years, the field of Development Communication has developed a bottom up approach in order to build a comprehensive program for stakeholders. The reason behind this approach is to generate participation among people who became their target. As a variant of participatory development, Focus Group Discussion has became an alternative for communication research method. In practice, Focus Group Discussion has great potential to achieve their optimum role. But, whoever employ this approach must also aware its limitations.